(untitled) (Global Journal of Human-Social Science, 2018)
An ancient Chinese parable tells of a poor young farmer who lost his only possession the horse that he had inherited from his father The members of the village visited the poor farmer and expressed their condolences for his loss How do you know that losing my horse was a misfortune Sure enough about a week later the horse returned with a healthy young mare as its wife The citizens of the village were shocked and they all went to visit the farmer to congratulate him on his good fortune How do you know that gaining the mare is good fortune Again the young farmer s words rang true About two weeks later as he was breaking the mare she threw him and he broke his leg All the people of the village gathered around his bed to console him for his tragedy How do you know that breaking my leg was a tragedy Later that month the Japanese invaded The emperor sent emissaries to every village to find healthy young men All the young men of the village were sent to the front except the young farmer whose leg had not yet healed None of the young men returned all were killed in battle And so it is with terrorism We see violence on the news and just accept that it is what the mainstream media and politicians tell us never once considering that it may be something else entirely